Does nomenclatural stability justify para/polyphyletic taxa? A phylogenetic classification in the xeric clade Pitcairnioideae (Bromeliaceae). Issue 5 (4th July 2019) - Gomes-Da-Silva, JanaÍna; Santos-Silva, Fernanda; Forzza, Rafaela Campostrini
Abstract : The genera Deuterocohnia, Dyckia, and Encholirium are recognized as the xeric clade Pitcairnioideae. More than 220 xeric species of this group occur in South America in the Andean region, the Chacoan subregion, and the South American Transition Zone. The species recently and rapidly diversified, and such phylogenetic relationships are difficult. This clade is well-supported in phylogenetic analyses, but despite the monophyly of this group of xeric species, the analyses have demonstrated the paraphyly or polyphyly of genera in the xeric clade. However, most of these studies suffer with partial resolution, limited taxon sampling or incorrect homology statements. To investigate this group, we conducted the most comprehensive phylogenetic analysis of the xeric clade to date using parsimony criteria with morphological and molecular datasets, including plastid and nuclear genomes concatenated for the first time, to establish a suitable classification. A total of 133 accessions were included that corresponded to 109 taxa. The dataset included 70 morphological characters and ∼6 kb of sequence data from the plastid and nuclear genomes. Phylogenetic analyses were conducted using equal and implied weighting. The analysis resulted in a well-supported cladistic hypothesis and demonstrated the three genera as currently circumscribed are not supported as monophyletic. Based on the results we propose a new classification that reflects the evolutionary relationships, a new circumscription for Dyckia is proposed that includes the species belonging to Deuterocohnia and Encholirium . For this circumscription, 41 combinations were made for Dyckia .